Biological properties of Moringa oleifera: A systematic review of the last decade [version 1; peer review: 2 approved, 1 approved with reservations] - Andrea Catalina Gómez; Javier Andrés Soto; C. A. Zuniga-Gonzalez; Karen Shirley Molina; Andrea Natalia Barreto; Maryeli Vásquez (F1000Research)
Background The growing incidence of chronic diseases such as cancer and the emergence of drug-resistant microorganisms constitute one of the greatest health challenges of the 21st century. Therefore, it is critical to search for new therapeutic alternatives. Moringa oleifera is a plant well known for the properties of its phytocomponents and its role has been analyzed in a variety of fields, from medicine to biotechnology. Methods In this work, the biological activity of Moringa oleifera in human health was explored through a review of 129 original articles published between 2010 and 2021 related to antitumor activity and its potential uses against chronic and infectious diseases. Results Moringa oleifera extracts showed antioxidant, hypoglycemic, antihypertensive and cytoprotective properties at neuronal, hepatic, renal and cardiac levels. Besides, cytotoxic effects, apoptotic and antiploriferative activity against several cancer cell lines has been demonstrated. On the other hand, the antimicrobial potential of M. oleifera was also evidenced, especially against multidrug-resistant strains. Conclusions Hence, it is supported that there is a wide range of clinical entities in which Moringa oleifera exhibits significant biological activity that could contribute to counteracting metabolic, infectious and chronic diseases in a similar or improved way to the drugs traditionally used.